Innovation of Course System for Metallurgical Technology Specialty Combining Engineering With Study - Wu, Yang (Journal of Theory and Practice of Social Science, 2024)
With the continuous development of social economy and science and technology, my country's education has also undergone various changes. In order to meet the requirements of the current society, metallurgical technology education in higher vocational colleges must improve the teaching quality from the innovative curriculum system. Vocational colleges themselves are places for cultivating talents for social enterprises, so only by perfecting the curriculum system can the comprehensive ability of students be improved from diversified education. the effective innovation of the curriculum system requires the construction of the higher vocational curriculum system in the mode of combination of work and study. This article mainly focuses on the analysis and research on the innovation of the combined engineering and course system for metallurgical technology majors.